The Effect of Socio-Demographic and Obstetric Factors on Early Initiation of Breastfeeding in Tegal District, Central Java - Nisa, Juhrotun; Salimo, Harsono; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2017)
Background:ÃÂ It is estimated that approximately 10 million children die every year worldwide. Forty five percent of those deaths are caused by malnutrition either directly or indirectly. Studies have shown that breastfeeding in the first hour can reduce neonatal death to 22%. However, breastfeeding practice in the first hour of life reaches only 43% of the newborns in the world. In South Asia, early initiation of breastfeeding is only 41% of the newborn, while in Indonesia it is only 34.5%. This study aimed to determine the effect of socio-demographic and obstetric factors on early initiation of breastfeeding in Tegal District, Central Java.Subjects and Method:ÃÂ This was an analytic observational study with cross-sectional design. This study was conducted at 4 Community Health Centers (Puskesmas Pagiyanten, Puskesmas Pagerbarang, Puskesmas BumÃÂijawa, Puskesmas Jatinegara) and Dr. Soeselo hospital, Tegal District, Central Java, from February to March 2017. A sample of 121 post partum mothers were selected for this study by ÃÂ exhaustive sampling. The dependent variable was time from birth delivery to breastfeeding. The independent variables were maternal education, maternal employment status, maternal knowledge, family income, parity, antenatal care (ANC) visit, and health provider support. The data were collected by questionnaire and were analyzed by multiple logistic regression.Results:ÃÂ Early initiation of breastfeeding was positively affected by maternal education Ã¢â°Â¥ High School (OR=3.90; 95% CI=1.14-13.37; p=0.030), maternal work outside the house (OR=7.93; 95% CI=1.68 to 37.52; p=0.009), ANC Ã¢â°Â¥ 4 times (OR=3.48; 95% CI=0.82 to 14.81; p=0.092), and strong ÃÂ health provider support (OR=12.58; 95% CI=4.30 to 36.77; p<0.001)Conclusion:ÃÂ Early initiation of breastfeeding is positively affected by maternal education Ã¢â°Â¥ High School, maternal work outside the house, ANC Ã¢â°Â¥ 4 times, and strongÃÂ  health provider support.Keywords:ÃÂ Socio demographic, obstetric factor, early initiation breastfeedingCorrespondence:ÃÂ Juhrotun Nisa. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: nisa.jn20@gmail.com. Mobile: +6285642905995.ÃÂ Journal of Maternal and Child Health (2017), 2(2): 89-99https://doi.org/10.26911/thejmch.2017.02.02.01